2016
DOI: 10.1016/j.icheatmasstransfer.2016.05.029
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on thermal conductivity of F-MWCNTs–Fe 3 O 4 /EG hybrid nanofluid: Effects of temperature and concentration

Abstract: In this paper, an experimental study on the effects of temperature and concentration on the thermal conductivity of f-MWCNTs-Fe 3 O 4 /EG hybrid nanofluid is presented. The experiments were carried out for solid volume fraction range of 0 to 2.3% in temperatures ranging from 25°C to 50°C. The results revealed that the thermal conductivity ratio enhances with increasing the solid volume fraction and temperature. Results also showed that, at higher temperatures, the variation of thermal conductivity ratio with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(47 citation statements)
references
References 35 publications
(34 reference statements)
1
46
0
Order By: Relevance
“…Usually, a nanofluid is composed of water (an ordinary fluid) mixed with nano-sized solid particles with high conductivity, which improves the thermal conductance properties of the fluid. It has been shown that nanofluids can potentially have a higher heat transfer coefficient, which results in a decrease in the size of thermal energy systems [5][6][7][8]. Over two decades of research and development, various types of nanomaterials, such as Al 2 O 3 , CuO, MgO, and Fe 3 O 4 , and different kind of base fluids, such as water, engine oil, ethylene glycol, therminol 66, have been experimented on.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, a nanofluid is composed of water (an ordinary fluid) mixed with nano-sized solid particles with high conductivity, which improves the thermal conductance properties of the fluid. It has been shown that nanofluids can potentially have a higher heat transfer coefficient, which results in a decrease in the size of thermal energy systems [5][6][7][8]. Over two decades of research and development, various types of nanomaterials, such as Al 2 O 3 , CuO, MgO, and Fe 3 O 4 , and different kind of base fluids, such as water, engine oil, ethylene glycol, therminol 66, have been experimented on.…”
Section: Introductionmentioning
confidence: 99%
“…It is of great importance to mention here, based on the previous literature review, that a few research articles consider thermophysical properties to be temperature independent, such as [21] and [45]. In contrast, many research papers consider thermophysical properties to be temperature dependent, such as [7], [8], [11], [24], [25], [30], [32], [34], [36] and [37] 3 HEAT TRANSFER ENHANCEMENT USING HYBRID NANOFLUIDS…”
Section: Thermophysical Properties Of Hybrid Nanofluidsmentioning
confidence: 99%
“…Some researchers prepare hybrid nanofluids by mixing two nanoparticles types, which separately synthesized within the base fluid. Harandi et al [11] employed the two-step method in preparing f-multiwall carbon nanotubes (MWCNTs)-Fe 3 O 4 / EG hybrid nanofluid. Dry f-MWCNTs and Fe 3 O 4 nanoparticles were mixed in ethylene glycol and were prepared in different volume fractions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the real magnetization values should be larger, where the measured values should be multiplied by the ratio of the total mass of the particle to the mass of the core ( ⁄ ). By calculating the average sizes of the core and the shell in each sample (from the HRTEM images) and by using a density of 5 g/cm 3 for the Fe3O4 core [27] and 1.13 g/cm 3 for the PEG coating [28], the calculated mass ratios ( ⁄ ) are 1.13, 1.11, and 1.097 for samples S1, S2, and S3, respectively. Two important results are obtained from the hysteresis loops presented in Figure 4 and the similar ones at higher temperatures; these are (a) the magnetization of all samples did not reach saturation at all temperatures, even at the maximum applied field of 3 T in our experiments, and (b) the openings of the hysteresis loops remain in all samples even at 300 K. The absence of saturation of the magnetization hints at surface spin effects.…”
Section: Magnetic Propertiesmentioning
confidence: 99%